Pendampingan Pengembangan Kurikulum PAUD Berbasis Budaya dan Kearifan Lokal di Desa Candikuning Kecamatan Baturiti Kabupaten Tabanan, Bali - Sutiyah Nova Irawati; Mukhammad Wahyudi; Anita Mauliyah; Ninik Kustini; Nur Fitrianti (LP3M IAIFA Kediri, 2025)
The purpose of this mentoring is to develop an early childhood education (PAUD) curriculum based on local culture and wisdom in Candikuning Village, Baturiti District, Tabanan Regency, Bali, using the Research & Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model approach. At the analysis stage, the identification of cultural values and local wisdom relevant to early childhood was carried out through observation and interviews with community leaders and early childhood educators. The design and development stages result in a thematic curriculum design that integrates elements of local culture. Then it is implemented in early childhood education institutions and evaluated through learning observation and feedback from teachers and parents. The results of the study show that the curriculum developed can increase children's involvement in learning and strengthen cultural identity from an early age. The ADDIE model has proven to be effective in producing a meaningful contextual and applicative curriculum for early childhood; At the same time, it is a tangible manifestation in maintaining local wisdom as the identity of the nation.